Analisis Dampak Pencemaran Limbah Industri PT. Boss Terhadap Kehidupan Masyarakat di Bandar Maruhur - Dian G Purba; Demak Purba; Dina Revani Saragih; Endang Silalahi; Grace Naibaho; Jelita Simbolon; Mei Meri C Damanik; Tia Amanda Saragih; Widiya Damanik; Yuri Varanti (STIKes Ibnu Sina Ajibarang, 2024)
Environmental problems are showing a significant increase day by day. The current environmental problem is one of the most urgent problems that needs to be resolved immediately, both from the government and from the surrounding community. Environmental pollution is formed from human activities which produce waste that enters the environment. Pollution carried out by PT. BOOS. Based on the data we submitted for research using a descriptive qualitative research method, this aims to describe a research phenomenon carried out in Bandar Maruhur, Simalungun Regency in May 2024. The establishment of factories in residential areas creates environmental instability due to toxic waste that has not been fully processed, creating biota. the river around the factory environment is disturbed. Apart from that, it also worsens the strong and unpleasant odor that often spreads around. Waste disposal activities by PT. BOSS, this unpleasant odor is often smelled around the environment. Pollution itself often disrupts community activities.